ISSUES OF ICT INTEGRATION IN RURAL SECONDARY SCHOOLS OF KAZAKHSTAN - A. Kurmangaliyev (Astana IT University, 2021)
The problem with attaining education equality for various categories of the population has been one of the priority topics of social and political studies. Kazakhstan has recently stated the aim to ensure equal access for all participants in the educational process to the best resources and technologies. However, half of all state schools are in rural areas and supporting them is often inadequate in comparison to urban schools. These schools have minimal infrastructure, for example, a lack of proper Internet access and professional development opportunities for teachers. The barriers to information and communication technologies in education seem to be one of the main issues for teaching staff in rural settings. The purpose of this research was to explore the issues of ICT integration in teaching and learning processes among secondary school teachers. This multiple case study explored the experiences of eight instructors from three rural schools through semi-structured interviews, lesson observations, and curriculum analysis. The results reveal evidence of the very poor quality of the Internet in visited rural schools. The findings also demonstrate that teachers often have to use their personal mobile phones at work despite the ban from administration. This, along with the poor technological capability of the schools, negatively affects the educational process in visited schools.